2008
DOI: 10.2220/biomedres.29.175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dried-bonito broth on mood states: A pooled analysis of four randomized controlled human trials

Abstract: Dried-bonito broth is commonly employed as a soup and sauce base in Japanese cuisine and is considered to be a nutritional supplement that promotes recovery from fatigue. Previous human trials have indicated that the ingestion of dried-bonito broth improves several mood states including fatigue, however, the effects in these studies have differed. The aim of this study was to clarify the effects of daily ingestion of dried-bonito broth on mood states by a pooled analysis of the randomized placebo-controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…BE was confirmed to be effective against mental fatigue, 29) and in this study we confirmed that BE is effective against physical fatigue. Our experiment results also clarified that the LMF of BE contains the active components.…”
Section: Discussionsupporting
confidence: 83%
“…BE was confirmed to be effective against mental fatigue, 29) and in this study we confirmed that BE is effective against physical fatigue. Our experiment results also clarified that the LMF of BE contains the active components.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the various amino acids contained in the DBB 12 , 15 cause this phenomenon. Interestingly, DBB has also been reported to improve fatigue, 15 mood, 16 and cognitive function 17 and has antioxidative properties, 18 and it might have contributed to maintain the patients’ general condition and prolong SOR treatment period. The limitation of our study is that it was designed as an exploratory and pragmatic clinical trial and has several methodological deficiencies with major group imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…DBB has also traditionally been considered a folk remedy for fatigue in the southern part of Japan. In previous works, DBB was confirmed to be effective against fatigue in animal and human studies (22,32). We demonstrated that the daily ingestion of DBB by humans improves mood, especially by alleviating mental fatigue (31), and that it increases performance on a simple calculation task (21).…”
Section: Introductionmentioning
confidence: 74%